Toxicity of atrazine and the products of its homogeneous photocatalytic degradation on the aquatic organisms Lemna minor and Daphnia magna - Klementová, Šárka; Hornychová, Lucie; Šorf, Michal; Zemanová, Jana; Kahoun, David (Environmental science and pollution research international, 2019)
Usage of atrazine, a widely used herbicide, is now banned in many countries. Although forbidden to use, significant concentration of this herbicide is still present in the environment. The study focused not only on the toxicity of atrazine itself but also on products of homogeneous photocatalytic degradation. Such degradation was very fast in given conditions (sufficient amount of Fe(III) in the reaction system)-more than 95% of the initial amount of atrazine was eliminated after 30 min of irradiation. The toxicity of atrazine and its photodegradation products were examined on the aquatic plant Lemna minor and microcrustacean Daphnia magna in both acute and chronic tests. While the growth inhibition assay of atrazine for Lemna minor revealed EC50 value of 128.4 μg dm-3, the herbicide did not affect Daphnia in the acute toxicity assay. A degradation product, desethyl-atrazine, has been demonstrated to have a pronounced negative effect on the plant growth. Both atrazine and desethyl-atrazine affect negatively the number of juveniles and number of clutches of Daphnia magna in the chronic toxicity assay. Photocatalytic degradation lowers the negative effect of atrazine in Daphnia magna while photodegradation products still negatively affect Lemna growth.
Keywords: atrazin; Daphnia magna; Triazine; Daphnia; Photodegradation products; Desethyl-atrazine; zvířata; Araceae; Aquatic Organisms; Ferric Compounds; Herbicide; Lemna minor; herbicidy; železité sloučeniny; Water Pollutants, Chemical; Atrazine; Herbicides; Animals; vodní organismy; Acute toxicity; chemické látky znečišťující vodu; Chronic toxicity